EVALUASI STATUS HARA PADA PENGGUNAAN LAHAN MULTIPLE CROPPING DI DATARAN RENDAH - Yogi Nirwanto; Anita Dwy Fitria; Rudhiana Salam (Agros Journal of Agriculture Science, 2024)
Evaluation of soil nutrient fertility is needed to inform the level of nutrient availability in the soil. This evaluation is intended to mitigate land degraded or critical land. So that the area of critical land can be reduced by carrying out land management to maintain soil fertility. This research was conducted on 3 land uses, (i.e. fields, orchad and rice fields) with multiple cropping and monoculture management. The research was carried out with 3 repetitions at 4 slopes (i.e.0-8%, 8-15%, and 16-25%). Soil samples were taken compositely at two depths (i.e.0-20 and 20-30 cm). The parameters analyzed was soil chemical properties (i.e.pH H2O, total N, available of P, K, Organic C, and C/N). The results showed that land use had a significant effect (p<0.05) on availability of organic C, while slope had no significant effect (p>0.05) on soil chemical properties variables. pH H2O was significantly correlated (p < 0.05) with organic C (r = 0.445), available P (r = 0.653), and available K (r = 0.543). Keywords: evaluation of nutrient fertility; multiple cropping; organic C INTISARIEvaluasi status kesuburan hara tanah dibutuhkan sebagai informasi tingkat ketersediaan hara pada tanah. Evaluasi ini dimaksudkan sebagai upaya memitigasi lahan terdegrdasi atau lahan kritis, sehingga luasan lahan kritis dapat berkurang dengan melakukan manajemen pengolahan lahan untuk tetap menjaga kesuburan tanahnya. Penelitian ini dilakukan pada 3 penggunaan lahan, yaitu ladang, kebun, dan sawah dengan pengelolaan multiple cropping dan monokultur. Penelitian dilakukan dengan 3 kali ulangan pada 4 kelerengan 0-8%, 8-15%, dan 16-25%. Pengambilan sampel tanah dilakukan secara komposit pada dua kedalaman yaitu 0-20 dan 20-30 cm. Parameter yang dianalisis adalah sifat kimia tanah berupa pH H2O, N total, P tersedia, K tersedia, C Organik, dan C/N.  Hasil penelitian menunjukkan bahwa penggunaan lahan berpengaruh nyata (p<0,05) terhadap ketersediaan C organik, sedangkan kelerengan tidak berpengaruh signifikan (p>0,05) terhadap variabel sifat kimia tanah. pH berkorelasi signifikan (p <0,05) terhadap C organik (r = 0,445), P tersedia (r = 0,653), dan K tersedia (r = 0,543). Kata kunci: c-organik; evaluasi kesuburan hara; multiple cropping